CenterScapes : waste landscapes into thriving communities - Hoetmer, Derek (Kansas State University, 2013)
Within the past decade, waste landscapes of decaying regional shopping centers and malls have been transformed into new buildings, streets, and towns— otherwise known as greyfield redevelopments. The most successful of these greyfield redevelopment projects are designed as vibrant town centers that exhibit traits of larger 24-hour cities. Unfortunately, landscape has been less relevant within these projects than they have in historical town center precedents. Landscape architecture originated from societal, cultural, and environmental needs and emerged as a profession to meet those needs. Theory, research, and design principles have emerged as well from studying the importance of landscape within the urban realm. Based upon the theory of Landscape Urbanism, landscape should be the primary element of urban order and that landscape architects possess the ability to enhance these multi-disciplinary projects. In CenterScapes, explorative design projects act as experimental subjects for a landscape architecture approach to current successful greyfield-redevelopment-into-town-center design. This masters project illustrates design research in theory, precedent, design principle, analysis, and explorative design through two applications. While both applications exhibit traits of a greyfield-redevelopment-into-town-center typology, one is designed solely by landscape architects and the other is designed by an interdisciplinary team represented by architectural, landscape architectural, and real estate development disciplines. This report functions to reveal the importance of strategically allocated and designed open space to act as catalysts for new town center developments.
Keywords: Landscape Architecture; Urban Design Competition; Urban Land Institute; Derek Hoetmer; Landscape Architecture (0390)